Community's knowledge need and knowledge sharing in Wikipedia. Issue 4 (23rd February 2018) - Pee, L.G.
Abstract : Purpose: In practice, showing the community's need for knowledge (e.g. listing requests for new articles) is used to drive knowledge sharing in Wikipedia. Yet, theoretical understanding of how it influences one's knowledge sharing is still lacking. The aim of this study is to develop a model of the influence and show that one takes others' utility into account (utility interdependence). Design/methodology/approach: The proposed model was tested with data collected in a survey of 323 Wikipedia users. Findings: Others' knowledge need affects one's perceived forgone benefit of free riding (i.e. a cost of knowledge sharing) and, thereby, increases the intention to share knowledge. Originality/value: This study contributes to research by identifying utility interdependence in knowledge sharing. For practice, the findings provide empirical support for the general belief that showing others' knowledge need is useful for promoting sharing.